Conscripting Imagination: The National “Duty” of William Blake’s Art - Saklofske, Jon (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis paper explores William Blake’s creative and commercial positioning relative to late-eighteenth-century galleries, exhibition culture and artistic spectacle. Demonstrating a desire to reintroduce originality into reproductive processes while also embracing the exaggerated and politicised rhetoric often associated with the spectacular visual displays of exhibition societies and new media diversions, Blake confronts modern spectacle with corrective spectacles of his own, bringing clarity, detail and focus to bear on otherwise unmanageable sights. By combining the vocabulary of modern visual spectacles with a dutiful commitment to the maintenance of national strength and progress in the advertisements for and descriptions of his 1809 exhibition, Blake optimistically reconfigures his public as a homogeneously capable body of intellectual and consumer ability. Viewing his own artistic assertion as dramatic performance on national and political scales, he appeals to spectatorial intellect in an era of increasingly sensationalist visual displays, individually attempting to reconfigure the taste of his beloved “public” through a seductive hybridization of spectacular novelty and gallery traditions. However, his “failed” exhibition allows us to see the overall incompatibility between his intended functions for art on national and political fronts (the conceptual), the rhetoric of spectacle (the visual), the individualism at the heart of Blake’s revolutionary nationalism and the persistent economical/commercial foundations of this project. Blake’s vision of a direct link between the strength of artistic expression, the potential of the urban audience and the strength of a nation is complicated by the economic demands faced by the artist and the inherently commercial nature of spectacle.